2022
DOI: 10.1097/dcr.0000000000002355
|View full text |Cite
|
Sign up to set email alerts
|

Novel Colorectal Endoscopic Submucosal Dissection With Double-Endoscope and Snare-Based Traction

Abstract: BACKGROUND: Colorectal endoscopic submucosal dissection is technically demanding, and the traction offered by gravity, cap, or clip-with-line during conventional endoscopic submucosal dissection remains unsatisfactory. Robotic systems are still under development and are expensive. We proposed double-scope endoscopic submucosal dissection with strong and adjustable traction offered by snaring the lesion with additional scope. OBJECTIVE: This study aimed to test the novel double-scope endoscopic submucosal dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…6 With conventional traction methods sometimes falling short, Chou et al introduced a novel double endoscopy ESD with snare traction. 7 The retrospective study showed a median procedure time of 32.45 min for double-scope ESD, significantly shorter than the 54.61 min for matched conventional ESD. All lesions were completely resected without major complications.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…6 With conventional traction methods sometimes falling short, Chou et al introduced a novel double endoscopy ESD with snare traction. 7 The retrospective study showed a median procedure time of 32.45 min for double-scope ESD, significantly shorter than the 54.61 min for matched conventional ESD. All lesions were completely resected without major complications.…”
mentioning
confidence: 87%
“…All lesions were completely resected without major complications. 7 Double endoscopy ESD can be used effectively to remove lesions in difficult anatomical areas. 8 Wu et al also proposed that the snare tip is a viable alternative tool for colorectal ESD in a specific population, particularly when specialized ESD knives are unavailable.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the double-scope traction technique, a second small-caliber endoscope is inserted along with the main endoscope after circumferential resection. By passing a share, net, or forceps through the second endoscope’s channel, and deploying the instrument of interest on the desired edge of tissue undergoing resection, traction can be applied ( 17 ). The primary endoscope is responsible for ESD.…”
Section: Non-robotic Endoscopic Tractionmentioning
confidence: 99%